A life in the struggle : Ivory Perry and the culture of opposition - Lipsitz, George (Temple University Press, 1995)
Now updated to include the final chapter of Ivory Perry's life, this new edition completes the life story of the grass-roots activist whose flamboyant direct action protests and patient behind the scenes organizing helped educate and agitate his community in the struggle for civil rights and economic opportunity.
Keywords: Perry, Ivory.; Perry, Ivory; African Americans -- Biography.; Civil rights workers -- United States -- Biography.; Civil rights movements -- United States -- History -- 20th century.; African Americans -- Civil rights -- Missouri -- Saint Louis.; Saint Louis (Mo.) -- Race relations.; Noirs américains -- Biographies.; Défenseurs des droits de l'homme -- États-Unis -- Biographies.; Mouvements des droits de l'homme -- États-Unis -- Histoire -- 20e siècle.; Noirs américains -- Droits -- Missouri -- Saint Louis.; BIOGRAPHY & AUTOBIOGRAPHY -- Political.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; SOCIAL SCIENCE -- General.; African Americans; African Americans -- Civil rights; Civil rights movements; Civil rights workers; Race relations; Missouri -- Saint Louis; United States; Biografie; 1900-1999; Biography; Biographies; History; Biographies.